Effectiveness of Mosquito Larvae Control Implemented by the Officers with Salary Payment - แสงพิศุทธ์ ธนวัน; บุญเรืองศรี มยุรี; ชาวนา นที; เปล้ากระโทก จำเริญ; ภักดีกิจ สนธยา (Disease Control Journal, 2010)
This study was a quasi experimental research and aimed to compare the reduction of house which found mosquito larvae before and after intervention in the villages which performed by mosquito larvae control officers with and without salary payment including to know the satisfaction of people and village committees to the mosquito larvae control activities and the reasonable salary to pay to the mosquito larvae control officers. The study area was composed of 3 the experimental villages where were implemented the mosquito larvae control by the officers with salary payment and 3 the control villages where were performed by ones without salary payment. The data was collected by mosquito larvae survey and interviewing and analyzed by descriptive and analytic statistics. The results revealed that the house index (HI) in the experimental villages before implementation was 14.23 and reduced to be 0 after implementation while in the control villages HI was 11.31 before implementation and decreased to be 4.52 after implementation. The house index (HI) of study villages which performed by the mosquito control officers with salary payment was decreased, during the last five months it was declined very dramatically (5.80, 3.29, 0.40, 0.81and 0 respectively) while in control villages HI was down gradually. The satisfaction of people to mosquito larvae control by officers with salary payment was in the highest level at all items while the village committee were satisfied to monitor these activities in the high level in all items. The reasonable salary in each district was different. It depended on various factors which should be studied further.